Novel Word Learning With Verbal Definitions and Images: Tracking Consolidation With Behavioral and Event‐Related Potential Measures. Issue 4 (26th June 2022) - Lei, Daisy; Liu, Yushuang; van Hell, Janet G.
Abstract: We examined the impact of images on novel word learning and consolidation, in a conceptual replication of Liu and Van Hell (2020). After participants had learned one set of novel words with definitions and images on Day 1 (remote words) and a different set on Day 2 (recent words), they judged the semantic relatedness of word pairs on Days 2 and 8 while event‐related potentials (ERPs) were recorded. Day 2 ERPs showed that remote, but not recent, novel words elicited a late positive component. By Day 8, both remote and recent novel words elicited a late positive component. We observed no N400 on either day. Comparing these learners (definition‐image group) with learners trained with definitions only (using data from Liu & Van Hell, 2020) revealed that the groups' ERP patterns did not differ, but definition recall and relatedness judgment performances were higher for the definition‐image group than for the definition‐only group. Learning novel word meanings through definitions and images strengthened behavioral outcomes but did not affect ERP signatures of learning and consolidation. Abstract :